2006
DOI: 10.1177/014556130608500716
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Dysplasia in the Retropharyngeal Area

Abstract: More fibro-osseous lesion s originate in the bones of the extremities than in the craniomaxillofacial bones, scapula, and ribs, which are rarely involved. Fibro-osseous lesions that decrease the quality oflife should be treated surgi cally. We report the case of a fibro-osseous lesion that caused globus pharyngeus and dysphagia. We discuss the clinical, radiologic, and histopathologic features of this case as well as the removal of this unusual lesion by Doppler ultrasound-guidedsurgery. Tothe bestofour knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A total of nine studies on FD/MAS were identified during our search (94)(95)(96)(97)(98)(99)(100)(101)(102). Three out of the nine studies were case-reports.…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
“…A total of nine studies on FD/MAS were identified during our search (94)(95)(96)(97)(98)(99)(100)(101)(102). Three out of the nine studies were case-reports.…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
“…Th e term fi bro-osseous lesion is a descriptive but diagnostically imprecise term that applies to a group of nonspecifi c tumors in which normal bone is replaced by collagen, fi broblasts, and varying amounts of osteoid or calcifi ed tissue. 1 Th e two most common types of fi bro-osseous lesions are fi brous dysplasias and ossifying fi bromas, which have similar histologic characteristics. [1][2][3] One of the confusing areas of pathology involves the examination of benign fi bro-osseous lesions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Th e two most common types of fi bro-osseous lesions are fi brous dysplasias and ossifying fi bromas, which have similar histologic characteristics. [1][2][3] One of the confusing areas of pathology involves the examination of benign fi bro-osseous lesions. 4 Making a careful diff erential diagnosis within this group of lesions is crucial because of the diff erences in their biologic behavior, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations